The Newmarket pump: a new suction pump for external negative pressure ventilation. - Kinnear, W J (1985)
A new electronically controlled pump has been developed for use with a cuirass in providing external negative pressure ventilation. It is smaller, lighter, and more versatile than currently available pumps and operates on a servo principle. A rotary valve between the pump and the cuirass varies the rate of extraction of air from the cuirass. The pressure within the cuirass is sensed by a pressure transducer, and the output of this is used to control the position of the rotary valve by means of a motor so that the pressure within the cuirass follows a predetermined half sine wave pattern. The respiratory rate varies from 10 to 30 per minute and the inspiratory to expiratory time (I/E) ratio from 3:2 to 2:3. Inspiratory pressure varies from 0 to -50 cm H2O and an expiratory pressure of 0 to +50 cm H2O can be imposed. The performance of the new pump was assessed in 21 patients with nocturnal hypoxaemia who were accustomed to external negative pressure ventilation. The mean tidal volume achieved increased with increase in cuirass suction pressure, and changing the I/E ratio from 1:1 to 3:2 produced a small increase at a cuirass negative pressure at 20 cm water. Comparison of the Newmarket pump with the Cape pump in 14 patients showed that similar tidal volumes were achieved. Overnight monitoring of cuirass pressure in one patient showed more even control of peak negative pressure with the Newmarket pump than with the Cape pump. Ten pumps are in use in patients' homes; five have been in service for more than six months and no important problems have been encountered. The new pump seems to offer advantages that make external negative pressure ventilation more acceptable.